Patterns of Advanced Computer Applications in Singapore - Han, Chun Kwong (1983)
This thesis analyzed the state of practice in Operations Research (OR) and Management Information Systems (MIS). Special emphasis is placed on the role of computer technology in these advanced application areas. A major finding of the research reported in this thesis is that both OR and computer-based MIS were used only by approximately a quarter of the survey samples. Operations Research was mainly applied to operational and tactical problems on an ad-hoc basis by various functional areas. The majority of the techniques were used regularly only by a third of the users. It was only with in the last five years that most of the OR techniques were implemented. Overseas headquarters and associates were the most frequent source initiating the use of operations research in Singapore. In contrast to practices in the West, OR has not suffered from lack of top management support. Management-oriented information systems were found in less than half of the electronics firms. An Information Systems (IS) Typology was developed to classify information systems of various degree of sophistication. Using this conceptual scheme, the analyses revealed that number of employees, product type, nationality, age, market and equity capital influenced the sophistication of information systems. The state of practice and development trends in computer based information systems were also examined. The survey found that the use of computers in information systems has been a recent phenomenon and computer impact was mainly felt in lower level management activities and in the accounting and logistics areas. In general, systems management activities were under the jurisdiction of the Accounting / Finance Department-traditionally the predominant location of systems activities. It is not expected that there will be large scale expansion in computer-based OR and MIS in the near future. The manority of OR techniques and applications will continue to be financial in nature, based essentially on an extension of the accounting system to generate information for management decision support. A general direction towards developing management-oriented in formation systems was identified in this research.